Observation of nonlinear input-output power characteristic of light emission from an electrically-biased metallic photonic crystal - Mei-Li Hsieh; Tyler Romero; J. A. Bur; Xuanjie Wang; Jhih-Sheng Wu; Shankar Narayan; Sajeev John; Shawn-Yu Lin (npj Nanophotonics)
Abstract We report, to the best of our knowledge, the first realization of an electrically-biased, resonant-cavity metallic photonic-crystal (PC) emitter. The PC device is electrically-biased and is driven out of thermal equilibrium. The PC emission exhibits a strongly nonlinear input-output power characteristic at the resonant peak wavelength, λ ~ 1.7 μm. Particularly, at lower bias, the emission power shows an exponential growth over 3 orders-of-magnitude. At higher bias, the growth slows down and shows a linear dependence on input power. This observed output/input characteristic may arise from non-equilibrium injection of hot electrons, the excitation of localized surface plasmons at the interior surfaces of the PC and photon emission to optical passband modes of the PC/ resonant cavity structure.